Effect of Hot Rolling on Microstructural Evolution and Wear Behaviors of G20CrNi2MoA Bearing Steel - Guanghua Zhou; Wenting Wei; Qinglong Liu (Metals, 2021)
Hot rolling can improve the mechanical properties after heat treatment by improving the microstructure. The effect of hot rolling (HR) deformation on the microstructural transformation of G20CrNi2MoA bearing steel in the subsequent CQT (carburizing-quenching and tempering) and RQT (reheating-quenching and tempering) processes was studied. The results indicate that the austenite grain size decreased by 20% after 45% hot rolling reduction, and the number of large-angle grain boundaries increased due to the recovery and recrystallization induced by hot deformation. The refinement effect of hot deformation on austenite grains was retained after dual austenitizing, and the large-angle grain boundaries and massive dislocation in the grains caused by hot deformation promoted the diffusion of carbon atoms during carburization, resulting in a higher surface carbon concentration. The refined grains and higher carbon concentration affected the volume fraction and size of undissolved carbides in RQT specimens. When the initial hot rolling reduction reached 45%, the average particle size of carbides decreased by 40%, and the area volume fraction increased by 37%. The Vickers hardness increased, but the friction coefficient and wear rate were significantly reduced with the increase in the initial hot rolling reduction. The main reasons for the improved wear resistance were fine grains, superior carbide distribution and high hardness.